A plastic wall tile and method of manufacturing thereof - Raja Abdullah, Raja Izamshah; Mohd Abid, Mohd Asyadi ‘Azam; Subramonian, Sivarao; Kasim, Mohd Shahir; Md Ali, Mohd Amran; Abu Bakar, Mohd Hadzley; Sulaiman, Mohd Amri; Mohamad, Effendi; Abdul Aziz, Mohd Sanusi; Hussein, Nur Izan Syahriah (2014)
The present invention provides a plastic wall tiles made of 100% recycled High Density Poly Ethylene (HDPE) bottle, liquid detergent bottle, bucket, house appliances etc. The tiles are very light in weight, tough in properties, having excellent impact and water resistance capacity, its highly durable, having good sliding and damping properties. The stylish luxurious pattern and texture design of tiles conveying elegance and tranquility to create custom experience.